Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem-Based Learning pada Elemen Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 di Kelas V SDN 20 Indarung Kota Padang - Yanti, Wella Asmada; Mansurdin; Anita, Yesi; Masniladevi (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to improve student learning outcomes in Pancasila Education, particularly on the elements of the 1945 Constitution of the Republic of Indonesia, through the application of the Problem-Based Learning (PBL) model. This study is a Classroom Action Research (CAR) conducted in two cycles, each including the planning, implementation, observation, and reflection stages. The research subjects were teachers and 29 fifth-grade students of SDN 20 Indarung, Padang City in the 2025/2026 academic year. Data collection techniques included observation of teacher and student activities, learning outcome tests, and documentation. The data obtained were analyzed using qualitative and quantitative approaches. The results of the study indicate that the application of the PBL model in learning the elements of the 1945 Constitution of the Republic of Indonesia is able to improve the quality of learning and student learning outcomes. The quality of the teaching module increased from the good category to very good. Teacher and student activities also increased in each cycle. In addition, student learning outcomes showed a significant increase from cycle I to cycle II and have achieved the established completion criteria. Based on these findings, it can be concluded that the PBL model is effective in improving student learning outcomes in Pancasila Education learning in Elementary Schools.